Norman and Anglo-Norman participation in the Iberian Reconquista c.1018 - c.1248 - Villegas-Aristizabal, Lucas (2007)
This thesis covers the Norman and Anglo-Norman contribution to the Iberian Reconquista from the early eleventh to the mid-thirteenth centuries. It explores the involvement of these groups as part of the changing ideas of Holy War and their transformation as result of the First Crusade. It shows that although the Reconquista was the result of important political and economic factors within the Iberian realms, the theological aura that the papacy started placing on this conflict was a powerful motivator increasing the interest of the Normans and later Anglo-Normans, especially when coincidental with the general call for crusade in western Europe that resulted in the large expeditions that are known to us as the crusades.